Wage Bargaining with Endogenous Profits, Overtime Working and Heterogeneous Labor - Mumford, Karen; Dowrick, Steve (The Review of Economics and Statistics, 1994)
This paper estimates the role of insider power in wage determination in a unionized industry, examining the direction and magnitude of biases that may arise through failure to control for variation in both hours of work and the composition of the labor force and through failure to control for the endogeneity of measured profits. Furthermore, by examining the extent to which rent-sharing is related to exogenous demand shocks rather than to potentially endogenous productivity, the authors provide a test of the bargaining and pure efficiency wage models, finding that the majority of the insider weighting can be explained by the bargaining model. Copyright 1994 by MIT Press.